Serum leptin level-insulin resistance-based correlation in polycystic ovary syndrome obese and non-obese sufferer female - Sharif, Yasamin Hamza (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Polycystic ovary syndrome (PCOS) is a well-globally-occurred heterogeneous endocrine disorder, affecting 5–10% of females with hyperandrogenism and prolonged anovulation.Objective: This work was done to understand the serum leptin role in women with PCOS in a link with the body mass index (BMI) and insulin resistance (IR).Patients and methods: This one-year-study was conducted in the Departments of Obstetrics and Gynecology as well as Infertility Unite in AL-Diwaniyah Maternity and Pediatrics Teaching Hospital, Iraq, in which 40 patients with PCOS as a (study group), and 40 healthy non PCOS patients as the (control group), after BMI assessment, both the study and control groups will further stratified into subgroups as normal weight and overweight patients’.  Blood samples were obtained for all patients for the serum leptin level (SLL) and fasting blood glucose (FBG) and serum insulin level, then HOMA-IR equation have been used to estimate insulin resistance for all patients.Results: SLL of the PCOS women (mean ±SD, 22.29±10.96 ng/ml) was significantly (p